Sequential drinking water sampling as a tool for evaluating lead in flint, Michigan. (15th June 2019) - Lytle, Darren A.; Schock, Michael R.; Wait, Kory; Cahalan, Kelly; Bosscher, Valerie; Porter, Andrea; Del Toral, Miguel
Abstract: Eliminating the sources of human lead exposure is an ongoing public health goal. Identifying the make-up of household plumbing and service line material type is important for many reasons including understanding lead release sources and mechanisms, targeting locations for lead service line (LSL) removal, and assessing the effectiveness of lead remediation strategies. As part of the response to Flint, Michigan's drinking water lead public health crisis, a return to their original drinking water source (Lake Huron) and an increase in orthophosphate dose was implemented in late 2015. In 2016, EPA performed multiple rounds of sequential or "profiling" water sampling to evaluate corrosion control effectiveness and identify lead sources in homes and service lines, as well as to evaluate the effectiveness of corrosion control treatment with time on the different plumbing components. The results showed that lead levels, including high lead levels likely associated with particles, decreased with time in homes sampled during the 11-month evaluation period. Although sequential sampling indicated that brass fittings, brass fixtures, and galvanized pipes were lead sources, LSLs were the greatest source of lead when present. Following the removal of LSLs, the total mass of lead contributed to the drinking water decreased by 86% on average. Highlights: Sequential Drinking Water Sampling as a Tool for Evaluating Lead in Flint, Michigan. Sequential or profile water sampling was used by the EPA to assess lead in Flint. Sequential sampling helped identify lead sources including buried public-side LSLs. Sequential sampling helped evaluate corrosion control and particle release over time. LSL removal reduced the lead contributed to the drinking water on average by 86%.